Estudo de possíveis correlações entre miastenia grave e exposiçao crônica a pesticidas em nosso meio - Camargo, Abigail [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the São Paulo state is very common application of pesticides in agriculture without protective equipment, with great exposure of workers to the toxic agents, and domestic use of insecticides is also widespread. Neuromuscular transmission defects with myasthenia related to the organophosphate pesticides were demonstrated in human and animals. The chemical group of pyrethrins and pyrethroids has action on the peripheral nervous system of insects and humans. The aim of this study was to search correlations between Myasthenia Gravis and chronic exposure to pesticides in our geographic region. Questionnaires were applied on exposure to pesticides in 217 patients with clinical and EMG diagnosis of Myasthenia Gravis, 163 women and 54 men, aged from 14-84 years, seen in two medical services of UNESP and UNIFESP, and in 227 controls, 179 women and 48 men, aged from 17-78 years. Data were statistically analyzed by the Association Chi-square test. The statistical analysis of all patients exposed or not exposed suggested possible association of myasthenia gravis with chronic exposure to pesticides (p <0.0001)

No estado de São Paulo é comum aplicação de pesticidas na agricultura sem equipamentos de proteção, com grande exposição dos trabalhadores aos agentes tóxicos. O uso doméstico de inseticidas também é muito difundido. Foram demonstrados defeitos da transmissão neuromuscular, com miastenia, relacionados a pesticidas organofosforados. Inseticidas do grupo químico das piretrinas e piretróides, de uso doméstico, atuam sobre o sistema nervoso dos insetos e dos seres humanos. O objetivo deste trabalho foi procurar correlações entre Miastenia Grave e exposição crônica a pesticidas em nosso meio. Foi aplicado questionário sobre exposição a pesticidas em 217 pacientes com diagnóstico clínico e ENMG de Miastenia Grave, sendo 163 mulheres e 54 homens, com idades de 14 a 84 anos, provenientes dos serviços médicos da UNESP e UNIFESP, e em 227 controles, sendo 179 mulheres e 48 homens, com idades de 17 a 78 anos. Os dados foram analisados estatisticamente pelo Teste de Associação do Qui-quadrado. A análise estatística do total de pacientes expostos e não expostos sugeriu possível associação de exposição a pesticidas com miastenia grave (p < 0.0001)
Keywords: Miastenia grave; Doenças neuromusculares; Pesticidas - Efeito fisiológico; Pesticides - Physiological effect; Myasthenia gravis